1985
DOI: 10.1093/infdis/151.2.236
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological Studies of EI Tor Cholera in Bangladesh: Association of Serum Antibody Levels with Protection

Abstract: In rural Bangladesh, family contacts of patients with cholera were studied prospectively to examine whether protection against colonization and disease due to Vibrio cholerae O1 was associated with circulating antibodies to V. cholerae. Family contacts (1,071) of 370 patients with cholera were visited daily for 10 days, cultured for V. cholerae, and queried about diarrhea. Sera collected on days 1 and 21 were assayed for vibriocidal antibodies, IgG and IgA antibodies to cholera toxin, and IgG antibodies to lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
168
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(172 citation statements)
references
References 19 publications
4
168
0
Order By: Relevance
“…The peak of bactericidal antibody activity occurred 2 weeks postvaccination, correlating with peak IgG levels and suggesting that S. Typhi-specific IgGs are largely responsible for complementmediated killing (31). Similar studies measuring vibriocidal antibody responses following exposure to V. cholerae implicated anti-LPS IgMs as the primary antibody subtype contributing to complement-mediated cell lysis (5,16,29,48). The IgM response to S. Typhi has heretofore been uncharacterized.…”
Section: Discussionmentioning
confidence: 89%
“…The peak of bactericidal antibody activity occurred 2 weeks postvaccination, correlating with peak IgG levels and suggesting that S. Typhi-specific IgGs are largely responsible for complementmediated killing (31). Similar studies measuring vibriocidal antibody responses following exposure to V. cholerae implicated anti-LPS IgMs as the primary antibody subtype contributing to complement-mediated cell lysis (5,16,29,48). The IgM response to S. Typhi has heretofore been uncharacterized.…”
Section: Discussionmentioning
confidence: 89%
“…10,17,18 Presumably, this increase over a lifetime is caused by frequent exposure to V. cholerae. The present study suggests that, in a highly cholera-endemic area, patients have exposures to V. cholerae sufficient to generate a vibriocidal response that begins as early as 6 months after an episode of severe cholera.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no threshold level of vibriocidal titer that confers complete protection from infection or symptoms, and the vibriocidal antibody is thought to be a surrogate marker of a protective mucosal immune response. [7][8][9][10] In areas where cholera is endemic, most residents have detectable vibriocidal antibodies by the teenage years, and titers increase with age. 10,11 Because of the background rate of vibriocidal antibodies in these populations, there is no threshold cutoff diagnostic of infection in an endemic area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no standard of care for the household members of patients, who are often at very high risk of developing a subsequent enteric infection. [13][14][15][16][17][18][19][20] A study in urban Dhaka, Bangladesh, found that household members of cholera patients had more than a 100 times higher risk of a cholera infection than the general population during the 1-week period after the presentation of the index cholera patient at the hospital. 21,22 Consistent with this finding, a recent study in rural Bangladesh found that the odds of a Shigella infection were 44 times higher for household members of pediatric shigellosis patient during this 1-week window.…”
Section: Introductionmentioning
confidence: 99%